1985
DOI: 10.1590/s0074-02761985000200016
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas e químicas do habitat da Biomphalaria tenagophila (Mollusca, Planorbidae)

Abstract: Samples of water and snails collected through aleatory scoops in a small dam were done to obtain data concerning the physical and chemical characteristics of the water and their possible influence on biological aspects of the life cycle of snails. Among the 17 analysed parameters, Alkalinity and Conductivity showed a positive correlation with the density of B. tenagophila (r = +0.224 and r = +0.290), while CO2 and Acidity were negatively correlated with this populacional parameter (r = -0.592 and 0.601). Alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the rainy season (May to August), Biomphalaria spp. populations decrease due to flooding, but there is accelerated snail growth and production of new individuals leading to repopulation of breeding sites, which mainly occurs at the end of the rainy season (September to December), when increasing the number of stagnant water (Paraense, 1972;Grisolia and Freitas, 1985;Juberg et al, 1987). Despite being basically harmful, established snail populations may flush out snails leading to the formation of new habitats (WHO, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…In the rainy season (May to August), Biomphalaria spp. populations decrease due to flooding, but there is accelerated snail growth and production of new individuals leading to repopulation of breeding sites, which mainly occurs at the end of the rainy season (September to December), when increasing the number of stagnant water (Paraense, 1972;Grisolia and Freitas, 1985;Juberg et al, 1987). Despite being basically harmful, established snail populations may flush out snails leading to the formation of new habitats (WHO, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to highlight that the present study was conducted over four years, which means that seasonal cycles, such as temperature and rainfall, for example, may have affected the abundance of mollusk populations 28,29 . This study revealed several water collections colonized by mollusks of the Biomphalaria genus, including streams, dams and waterfalls, which could serve for sporting practices or for the construction of pools, providing further sources of infection by schistosomiasis among tourists 4,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Another adaptation of molluscs is the acceleration of development during the rainy season to ensure the production of new individuals and thus the colony can withstand the next dry season. (Paraense, 1955(Paraense, , 1972Grisolia & Freitas, 1985;Juberg et al, 1987). The mollusc's reproductive mechanism has a fundamental role in the species' perpetuation.…”
Section: Molluscs Of the Biomphalaria Genusmentioning
confidence: 99%